KORELASI POLA MAKAN DAN KEJADIAN STUNTING PADA BALITA USIA 3-5 TAHUN DI INDONESIA - Nuraini, Novia; Batlajeri, Jomima; Suryati, Eros Siti; Hamidah, Hamidah (Jurnal Fisioterapi dan Kesehatan Indonesia, 2025)
Stunting is a disorder of growth and development of children due to chronic malnutrition and recurrent infections, which is characterized by or height is below standard. The period of 0-5 years is a very important period in life which is called the golden period in this period there is very rapid growth and development which will affect a child's future. Objectives Identify characteristics related to stunting incidents, identify eating patterns in toddlers aged 3-5 years, identify the correlation between eating patterns and stunting incidents. Methods: This study is a quantitative research type with a cross-sectional correlation approach. The population in this study were 97 toddlers. The sample in this study was 97 toddlers. Total sampling was taken with a research instrument using a questionnaire sheet. Results: Shows a high incidence of stunting as many as 44 toddlers representing (45.4%). Toddlers have poor eating patterns (69.1%). The results of the square test analysis P = 0.001. Conclusion: There is a relationship between toddler eating patterns and stunting incidents in the Bogor Health Center area. Suggestion: For health workers at the Health Center, provide more education and counseling regarding healthy and balanced eating patterns.